Clinical Evaluation of Intraoperative Near Misses in Laparoscopic Rectal Cancer Surgery. Issue 4 (April 2021) - Curtis, Nathan J.; Dennison, Godwin; Brown, Chris S. B.; Hewett, Peter J.; Hanna, George B.; Stevenson, Andrew R. L.; Francis, Nader K.
Abstract : Objective: To investigate the frequency, nature, and severity of intraoperative adverse near miss events within advanced laparoscopic surgery and report any associated clinical impact. Background: Despite implementation of surgical safety initiatives, the intraoperative period is poorly documented with evidence of underreporting. Near miss analyses are undertaken in high-risk industries but not in surgical practice. Methods: Case video and data from 2 laparoscopic total mesorectal excision randomized controlled trials were analyzed (ALaCaRT ACTRN12609000663257, 2D3D ISRCTN59485808). Intraoperative adverse events were identified and categorized using the observational clinical human reliability analysis technique. The EAES classification was applied by 2 blinded assessors. EAES grade 1 events (nonconsequential error, no damage, or need for correction) were considered near misses. Associated clinical impact was assessed with early morbidity and histopathology outcomes. Results: One hundred seventy-five cases contained 1113 error events. Six hundred ninety-eight (62.7%) were near misses (median 3, IQR 2–5, range 0–15) with excellent inter-rater and test–retest reliability (κ=0.86, 95% CI 0.83–0.89, P < 0.001 and κ=0.88, 95% CI 0.85–0.9, P < 0.001 respectively). Significantly more near misses were seen in patients who developed early complications (4 (3–6) vs. 3 (2–4), P < 0.001). Higher numbers of near misses were seen in patients with more numerous ( P = 0.002) and more serious early complications ( P = 0.003). Cases containing major intraoperative adverse events contained significantly more near misses (5 (3–7) vs. 3 (2–5), P < 0.001) with a major event observed for every 19.4 near misses. Conclusion: Intraoperative adverse events and near misses can be reliably and objectively captured in advanced laparoscopic surgery. Near misses are commonplace and closely associated with morbidity outcomes. Abstract : Supplemental Digital Content is available in the text